Diseño e implemetación de una red RoIP de dos vías para la empresa MaxiGroup - Suin Uyaguari, Danny Raúl (2016)
Possess more than an infrastructure for a communication system is a weakness that represent expenses for a company, this is the case of the enterprise MaxiGroup which has an internet service provider ISP and radio equipment for communication. The RF systems use the radio spectrum which is a limited resource; the implementation of this system is expensive because, for a number of radios, it is necessary to increase the capacity of the radio channel as well as repeaters, antennas, radios bases and end-point devices. Other kinds of communication are data networks which allows to send voice, data and video over a single infrastructure. Achieve convergence between radio systems, analog communication for voice and internet can be done through radio networks over Internet (RoIP). The RoIP network designed for MaxiGroup company achieves a saving of 39% compared to conventional analog radio systems communications and Its cost is $ 2,445.00. The RoIP network has a maximum jitter of 129 ms allowing voice communication among users without problem in different geographical location. The operation of the network RoIP is checked considering BER, bandwidth, transmission rate and channel capacity parameters